The new future perspective in corneal tissue utilisation - methods of preparation and preservation - Poláchová, Martina; Netukova, Magdalena; Benada, Oldrich; Kucera, Tomas; Kolin, Vojtech; Baxant, Alina-Dana; Sirolova, Zuzana; Studeny, Pavel (BMC ophthalmology, 2023)
PURPOSE: The goal of our study is to find an optimal approach to the preparation and preservation of corneal stromal tissue. We want to compare different methods of corneal stromal tissue creation and storage to optimize the efficacy of this process under the conditions of an eye bank. After we find the most suitable method to create a safe high quality product, we want to prove the possibility of using a single donor cornea for more than one patient. We would also like to verify the feasibility of making more corneal lenticules after the removal of a corneal endothelium for DMEK transplantation. METHODS: We provided morphological (histology, scanning electron microscope) and microbiological analysis in order to compare different methods of corneal lenticule and corneal stromal lamellae preparation and preservation. We also tested the surgical handling of the tissue to secure a safe manipulation of the tissue for clinical use. We compared two methods of corneal lenticule preparation: microkeratome dissection and femtosecond laser. As methods of preservation, we tested hypothermia, cryopreservation at -80 degrees Celsius in DMSO (dimethyl sulfoxide) and storage at room temperature with glycerol. Some intrastromal lenticules and lamellae in each group were previously irradiated with gamma radiation of 25 kGy (KiloGray). RESULTS: Corneal stromal lamellae prepared with a microkeratome have a smoother cut - side surface compared to lamellae prepared with a femtosecond laser. Femtosecond laser preparation caused more irregularities on the surface and we detected more conglomerates of the fibrils, while lamellae made with microkeratome had more sparse network. Using femtosecond laser, we were able to make more than five lenticules from a single donor cornea. Gamma irradiation led to damage of collagen fibrils in corneal stroma and a loss of their regular arrangement. Corneal tissue stored in glycerol showed collagen fibril aggregates and empty spaces between fibrils caused by dehydration. Cryopreserved tissue without previous gamma irradiation showed the most regular structure of the fibrils comparable to storage in hypothermia. CONCLUSION: Our results suggest that formation of a corneal lenticule lamellae by microkeratome results in smoother corneal lenticules, while being much cheaper than formation by femtosecond laser. Gamma irradiation of 25 kGy caused damage of the collagen fibres as well as their network arrangement, which correlated with loss of transparency and stiffer structure. These changes impair possible surgical utilisation of gamma irradiated corneas. Storage in glycerol at room temperature and cryopreservation had similar outcomes and we believe that both methods are appropriate and safe for further clinical use .
Keywords: Glycerol; Collagen; glycerol; Cornea; hypotermie; lidé; stroma rohovky; kolagen; dimethylsulfoxid; Hypothermia; Dimethyl Sulfoxide; Corneal Stroma; rohovka; Humans